‘I Don't Think There Is a One‐Size‐Fits‐All’: A Qualitative Study Exploring Healthcare Professional and Service Provider Perspectives of Using Innovative Models of Cervical Screening to Improve Equitable Access to Self‐Collection - Claire Bavor; Tessa Saunders; Mikayla Wolfe; Megan A. Smith; Nicola Creagh; Deborah Bateson; Angela Kelly‐Hanku; Paula Jops; Marion Saville; Natalie Taylor; Kate Broun; Julia M. L. Brotherton; et al. (Cancer Medicine)
ABSTRACT Introduction In the Australian National Cervical Screening Program (NCSP), self‐collection can be performed in any setting deemed appropriate by the healthcare professional who orders the test, creating opportunities to develop innovative cervical screening models that can address known barriers to access for under‐ and never‐screened women and people with a cervix. This study explored the acceptability and appropriateness of innovative models and key considerations for their design and implementation from the perspectives of clinical and non‐clinical providers. Methods We conducted online, semi‐structured interviews with healthcare professionals, pathology providers and community service providers (June–October 2023). Data were analyzed using template analysis, a form of thematic analysis. Results There were 132 participants from across Australia (82 clinical providers [e.g., doctors, nurses, midwives]; 34 non‐clinical providers [e.g., health/community service staff, disability support workers, bicultural workers]; and 16 pathology sector professionals). Four overarching themes were identified: acceptability, appropriateness, screening quality and safety, and implementation considerations. Most found innovative models acceptable when appropriately tailored to the needs of different population groups, particularly through community outreach, home in‐reach and peer‐supported services. Embedding clinical governance and oversight in the cervical screening pathway was a high priority to ensure that screening participants received adequate information about cervical screening and appropriate follow‐up care. Participants identified the need for clearly defined roles in the cervical screening pathway, sustainable funding and professional development opportunities to expand the role of nurses and optimize the roles of non‐clinical providers. Conclusions Innovative models of cervical screening using self‐collection can offer more accessible, inclusive, and convenient care, especially for under‐ and never‐screened populations. Clinical governance and oversight must be embedded in the cervical screening pathway to maintain high‐quality screening services and to support the implementation of tailored and targeted innovative screening models.